Meningkatkan Kemampuan Motorik Halus Melalui Kegiatan Melipat Untuk Anak Paud Kelompok B - Qorri Amami; Azizah Amal; Andryani Akib Akib (Universitas Negeri Makassar, 2022)
This study aims to improve fine motor abilities through folding activities. The method uses quantitative data analysis and descriptive percentage analysis to process existing data to get answers to the problems to be solved. The population in this study was group B children of TK Muslimat Nu 135 Berbek, as many as ten children, consisting of 3 boys and seven girls. This study is designed as a repeating cycle until the target is met. Based on the analysis of activity data folded in the first cycle by 10% with the number of 3 children completed. Because it has not met the target, this study continues in the second cycle, 60%, with the number of 6 children who can independently. This research continues until cycle III when the completion rate results are 100% and have met the target. Then this PTK was declared victorious. This study concludes that as many as ten children can be carried out through folding activities to improve fine motor skills in group B children in Nu 135 Berbek Muslimat Kindergarten.